Toxicological study of the matured seeds of dioclea reflexa on some biochemical and haematological parameters and histopathology of liver and kidney in mice - K. A. Adepoju , G.; Olaniyi, Femi (International Journal of Pharmacology and Toxicology, 2024)
This study was carried out to test the potential toxic effects of the consumption of the seeds of D. reflexa on haematological and biochemical parameters and hence, histological examination of the vital organ of the kidney and the liver was carried out. Thirty matured Wistar rats of both sexes were treated with oral repeated doses (2g, 3kg and 4kg /kg body weight) once daily of the matured seed flour of D. reflexa. The result showed that D. reflexa seed flour did not negatively impact on the haematological and biochemical parameters. Histological examination of the liver showed that the liver tissue components were normal in all the doses administered However, there was haemorrhage of blood into the tissue component of the kidney above 2g/kg/body weight while at 4g/kg/body weight, apart from haemorrhage of blood into the tissue component of the kidney, eosinophils materials could also be observed and the kidney functions were seriously impaired and performed below normal. It was concluded that D.reflexa possessed no toxicological property at low doses of 2g/kg/body weight as all the animals survived throughout the experiment. The seed flour could be considered safe on acute oral administration at this low dose where it did not impact negatively on the haematological and biochemical parameters.